(untitled) (Conferencea, 2024)
The article mentions that the development of tourism has a great impact on the local infrastructure: transport, telecommunications and other systems. It is also given that tourism directly participates in the formation of the country’s national income. Along with this, numerical data on the income from the tourism economy in the countries of the world are provided. It is mentioned about the important role of tourism in the country’s economy. And especially in employment and investment attraction. The article also mentions that the tourism development strategy in Georgia is based on the globally recognized principles of sustainable development of tourism, at the same time, its great potential in increasing the country’s income and the existence of reserves for equalizing the level of regional economic development and stimulating the development of other sectors of the economy are indisputable.